2020
DOI: 10.1186/s12891-020-3057-3
|View full text |Cite
|
Sign up to set email alerts
|

MRI-detected spinal disc degenerative changes in athletes participating in the Rio de Janeiro 2016 Summer Olympics games

Abstract: Objective: To describe the frequency and the distribution of degenerative disc disease (DDD) detected in athletes who underwent spine MRI in the 2016 Summer Olympic Games in Rio de Janeiro. Methods: Data on spine MRI examinations from the 2016 Summer Olympics were retrospectively analyzed. We assessed the frequency of DDD of the cervical (Cs), thoracic (Ts), and lumbar (Ls) spine using Pfirrmann's classification. Grade II and III were considered as mild, grade IV as moderate, and grade V as severe disc degener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…Neck Up to 87% of asymptomatic individuals may have bulging discs, 107 with 58% of younger, asymptomatic athletes showing cervical disc degeneration. 108…”
Section: Body Part Prevalencementioning
confidence: 99%
“…Neck Up to 87% of asymptomatic individuals may have bulging discs, 107 with 58% of younger, asymptomatic athletes showing cervical disc degeneration. 108…”
Section: Body Part Prevalencementioning
confidence: 99%
“…The researchers verified that Pfirrmann grades II and III are mild because there is no loss of disc space height. Pfirrmann grade IV is regarded as moderate because of reducing intervertebral disc height and grade V is considered, and the disc had space collapse [ 17 ]. This criterion is a useful scoring tool to access IVDD.…”
Section: Methodsmentioning
confidence: 99%
“…Also, a retrospective review of patient data suggested that Olympic Games athletes had a high number of degenerative disc diseases of cervical and lumbar spines on their MRIs. However, the athletes were symptomatic and did not include specifically runners [12].…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
“…There are conflicting results with firstly, positives outcomes in intervertebral disc health [9,10] in middle-aged endurance runners with a long history of running and high weekly mileage [3]. And secondly, negative outcomes in moderate-intensity running resulting in intervertebral disc compression in young adults [11] and spinal disc degenerative changes in Olympic athletes [12]. However, the study on Olympic athletes shows the importance of sequential MRI scanning and recruitment of asymptomatic participants, as many had a history of previous injuries which could have made them more vulnerable to degenerative changes [12].…”
Section: Introductionmentioning
confidence: 99%